What We Owe to Donald Schön: Three Educators in Conversation - MacKinnon, Allan; Clarke, Anthony; Erickson, Gaalen (Phronesis)

(untitled) (Institut de recherche sur les pratiques éducatives, 2013)
Readers with even a casual acquaintance with the research literature in the field of teacher education over the past 25 years will be aware of the dramatic increase in the use of the term ‘reflection’ to describe desired attributes [outcomes/behaviours] of participants in professional development programs for both novice and experienced teachers. Our intent is to draw upon our own collective experiences in our research and teaching practices to map out how and why we initially became intrigued with the many meanings associated with the term and how our understandings have changed over the past 25 or so years. We think that this type of ‘reflection-upon-experience’ is best revealed through the use of a narrative style and therefore we deliberately use a conversational format to convey our story.